A Novel Tax-Responsive Reporter T-Cell Line to Analyze Infection of HTLV-1 - Heym, Stefanie; Krebs, Pauline; Ott, Kristin; Donhauser, Norbert; Kemeter, Laura; Simon, Florian; Millen, Sebastian; Thoma-Kreß, Andrea (Pathogens, 2024)
Human T-cell leukemia virus type 1 (HTLV-1) infects CD4+ T-cells through close cell–cell contacts. The viral Tax-1 (Tax) protein regulates transcription by transactivating the HTLV-1 U3R promoter in the 5′ long terminal repeat of the integrated provirus. Here, we generated a clonal Tax-responsive T-cell line to track HTLV-1 infection at the single-cell level using flow cytometry, bypassing intracellular viral protein staining. Jurkat T-cells stably transduced with the SMPU vector carrying green fluorescent protein (GFP) under control of 18 × 21 bp Tax-responsive element repeats of the U3R were evaluated. Among 40 clones analyzed for Tax responsiveness, the top two were characterized. Upon overexpression of Tax, over 40% of the cells showed GFP positivity, and approximately 90% of the Tax-positive cells were GFP-positive, indicating efficient reporter activity. However, with CREB-deficient Tax mutant M47, both total GFP-positive cell counts and those within the Tax-positive group significantly decreased. Co-culture with chronically HTLV-1-infected MT-2 or C91-PL cells led to an average of 0.9% or 2.4% GFP-positive cells, respectively, confirming the suitability to monitor HTLV-1 transmission and that HTLV-1 infection is very low. Thus, the novel Tax-responsive reporter T-cell line is a suitable tool to monitor infection of HTLV-1 on the single-cell level.
CRIS-Team Scopus Importer:2024-12-06
Keywords: HTLV-1; HTLV-1 cell-to-cell transmission; HTLV-1 promoter; infection; reporter T-cell line; SMPU; Tax; Tax-responsive element; U3R